2019
DOI: 10.1080/15592324.2019.1642037
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation regulates the activity of INDETERMINATE-DOMAIN (IDD/BIRD) proteins in response to diverse environmental conditions

Abstract: INDETERMINATE-DOMAIN proteins (IDDs) belong to a diverse plant-specific family of transcriptional regulators that coordinate distinct functions during plant growth and development. The functions of several of these IDD members are transcriptionally regulated, but so far nothing is known about the regulation at the post-translational level in spite of the fact that post-translational modifications of these proteins have been reported in several large-scale proteomics studies. Recently, we showed that IDD4 is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Ubiquitination plays an important role in protein degradation, and phosphorylation controls the biological activity of proteins and plays a pivotal role in many biochemical processes [ 36 ]. In this study, and our previous work [ 22 ], 1184 phosphorylated proteins and 1515 ubiquitylated proteins were identified in petunia corollas following ethylene or air treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination plays an important role in protein degradation, and phosphorylation controls the biological activity of proteins and plays a pivotal role in many biochemical processes [ 36 ]. In this study, and our previous work [ 22 ], 1184 phosphorylated proteins and 1515 ubiquitylated proteins were identified in petunia corollas following ethylene or air treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Plant hormones, as important signaling molecules, can control plant growth, development, and stress responses [ 36 ]. Previous research has reported that many IDDs are related to hormone homeostasis [ 12 , 37 , 38 ]. For example, IDD14, IDD15, and IDD16 can cooperatively function in lateral organ morphogenesis and gravitropism through accelerating auxin synthesis and transport in Arabidopsis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except for the zinc finger domain, the IDD proteins owned two conserved amino acid residues (Ser73 and Ser182): Ser73 could be phosphorylated by MPK6 [ 38 ], and Ser182 has been reported to be modified by AKIN10 (the catalytic subunit of SnRK1) [ 37 ]. Here, all 22 ZmIDDs have Ser73 and Ser182 ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…are some of the TFs that show a strong association with salt-stress responses ( Chen et al., 2002 ; Singh et al., 2002 ). The IDD family of transcription factors regulate several biological processes in plants ( Kumar et al., 2019 ) and several phosphoproteomic studies have identified IDD transcription factors as targets for phosphorylation ( Völz et al., 2019c ).…”
Section: Introductionmentioning
confidence: 99%